Implementasi Zakat Maal secara Produktif, Solusi Pengentasan Kemiskinan di Kota Medan - Kurnia Sandi Panjaitan; Khairunisah Khairunisah; Nurul Jannah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to provide an overview in the orm of a portrait of zakat maal and how its contribution, role, and performance in alleviating poverty. The research method used in the journal is a qualitative method using zakat maal as a case study. Zakat maal is a system in the Qur’an to regulate several provisions regarding assets that must be tithe. Zakat is only prouctive as a qualitative and quantitative embodiment so that the zakat issued is not to meet needs at any time (comsumtive). However, trying to have an investment value for the independence of zakat recipients. In Indonesia, where most of the population is Muslim, it actually has stategic potential and is very feasible to be developed in driving the economy. In addition, the concept of zakat offered by Islam promises the dimensions of benefit and the management of potential economic resources in people’s lives so that poverty can be eradicated. Keywords: Zakat Mal, Productive Zakat, Proverty, Economy.